The Laboratory Medicine Inference Framework: evidentiary boundaries from measurement to clinical action - Raúl Rigo-Bonnin; Lídia Martínez-Zamorano; Virgínia Mas-Bosch; Míriam Valbuena-Asensio; Aurora Blanco-Font (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Introduction Laboratory medicine relies on multiple metrological, analytical, interpretative, and clinical frameworks. Although each addresses a specific question, the relationships linking measurement, interpretation, clinical translation, and action remain incompletely articulated. This fragmentation may encourage inferential overreach, whereby evidence is used to support conclusions beyond the question, intended use, population, or context it can legitimately address. Content This Opinion Paper proposes the Laboratory Medicine Inference Framework (LMIF), which organises laboratory medicine concepts into five interconnected domains: metrological and analytical foundations; clinical traceability and transferability; result interpretation; clinical translation; and clinical action. Concepts are assigned according to their predominant inferential role while recognising cross-domain dependencies. Two complementary pathways connect the domains: an evidence-to-action pathway towards broader and increasingly context-dependent conclusions, and an intended-use-to-requirements pathway through which clinical needs inform interpretive, transferability, and analytical requirements. Examples involving analytical performance specifications, measurement uncertainty, reference intervals, clinical decision limits, method comparability, compatibility, equivalence, interchangeability, clinical validity, and clinical utility illustrate the framework’s inferential boundaries. Summary The LMIF is underpinned by the Principle of Inferential Sufficiency: a conclusion is justified only when the available evidence adequately addresses the relevant inferential question, intended use, population, and context. The framework complements rather than replaces existing models and provides a common language for identifying evidentiary requirements, transferability needs, and unsupported inferential transitions. Outlook Future work should evaluate whether the LMIF improves education, method implementation, quality management, scientific communication, clinical consultation, and value-based laboratory medicine, and whether its domains and operational questions require refinement across laboratory and clinical settings.